2003
DOI: 10.1242/jeb.00219
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of caged calcium in cilia induces ciliary reversal inParamecium caudatum

Abstract: Intracellular Ca 2+ concentration controls both the pattern and frequency of ciliary and flagellar beating in eukaryotes. In Paramecium, it is widely accepted that the reversal of the direction of ciliary beating (ciliary reversal) is induced by an increase in intra-ciliary Ca 2+ levels. Despite this, the Ca 2+ -sensitive region of the cilium that initiates ciliary reversal has not been clearly identified.We injected caged calcium into living P. caudatum cells and applied ultraviolet (UV) light to portions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
(29 reference statements)
2
20
0
Order By: Relevance
“…They found that basal regions are more sensitive than more distal ones. More recently, Iwadate [37] found by laser activation of caged Ca 2+ that the distal part of cilia also contains the Ca 2+ -sensitive machinery relevant for ciliary beat reversal.…”
Section: Where In the Ciliary Membrane Reside Voltage-dependent Ca 2+mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that basal regions are more sensitive than more distal ones. More recently, Iwadate [37] found by laser activation of caged Ca 2+ that the distal part of cilia also contains the Ca 2+ -sensitive machinery relevant for ciliary beat reversal.…”
Section: Where In the Ciliary Membrane Reside Voltage-dependent Ca 2+mentioning
confidence: 99%
“…Difficulties in determining precise free Ca 2+ concentrations, [Ca 2+ ], within cilia and flagella have several reasons, not only the small size, but also unknown diffusion effects [30] after passing Ca 2+ -channels whose distribution along the cilium is unknown (see "Section 4"), as is that of a still increasing number of Ca 2+ -activated and Ca 2+ -binding proteins (CaBPs) [31][32][33][34][35], not to speak of practical problems with fluorochrome analyses in these slender and highly motile structures. Alternative methods, like intracellular application of Ca 2+ chelators of different k D or local photoactivation of caged Ca 2+ , as it is widely used in exocytosis research [36], proved useful merely on a rather coarse scale, at best to compare proximal and distal regions of cilia in Paramecium [37].…”
Section: Introductionmentioning
confidence: 99%
“…The direction of ciliary beat in Paramecium cells is then reversed by a rise in intraciliary Ca 2+ concentration [Naitoh and Eckert, ; Naitoh and Kaneko, ; Iwadate, ]. We applied UV light to a small patch of cilia on a Paramecium cell that had been previously injected with NP‐EGTA medium (white circle in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The injected volume of medium was approximately 8 pl, corresponding to about 3% of the whole cell volume. Ultraviolet (UV) irradiation of the local area was performed according to the methods described previously [Iwadate, ; Iwadate and Nakaoka, ] with slight modifications. An inverted microscope (TE300, Nikon, Tokyo, Japan) was used throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…24 Therefore, most visible event with involvement of calcium signaling in Paramecium species is ciliary reversal which depends on the intracellular increase in Ca 2C concentration. 25 It has long been known that members of Paramecium species including P. bursaria exhibit galvanotaxis, a directed swimming of cells toward the electrode, induced in response to an applied voltage. 23,26 A pharmacological approach has revealed that T-type calcium channels are involved in galvanotactic movement of P. bursaria involving electrically forced ciliary reversal, as galvanotactic behavior was shown to be sensitive to a variety of Ca 2C -related inhibitors such as Ca 2C chelators, inhibitors of intracellular Ca 2C release (such as ruthenium red and neomycin), lanthanide ions (general calcium channel blockers), and inhibitors of T-type calcium channels (such as NNC 55-0396, 1-octanol and Ni 2C ), while inhibitors of Ltype calcium channels such as nimodipine, nifedipine, verapamil, diltiazem and Cd 2C all failed to block the galvanotactic movement of P. bursaria.…”
mentioning
confidence: 99%